Absolute stress field measurement in structural steel members using the Lcr wave method. (July 2018) - He, Jingbo; Li, Zuohua; Teng, Jun; Li, Ming; Wang, Ying
Highlights: A method to measure the stress field in a steel member using Lcr wave is proposed. A sensor group is designed to transmit and receive the Lcr waves. Calibration of the SATD factor in different Lcr wave path is a necessary step. The unknown Lcr wave path stress can be calculated using the measured region stress. The method can characterize the stress distribution and extremum of a steel member. Abstract: The absolute stress in structural steel members is an important indicator of the performance of steel structures. Among the existing non-destructive testing (NDT) methods, ultrasonic methods have received the most research attention. The existing ultrasonic methods can evaluate the average stress in a fixed acoustic path but cannot easily measure the stress field within the tested objects. We present a non-destructive method to evaluate the absolute stress field in a structural steel member using longitudinal critically refracted (Lcr) waves. Specifically, a theoretical expression is derived for absolute stress measurement. A measurement system is developed to demonstrate the performance of the proposed method. A sensor group, which contains one transmitter and two receiver transducers connected by a Vernier calliper, is designed to transmit and receive Lcr waves. The proposed method is applied to two steel members with variable cross-sections. The traditional strain gauge method is used for verification. The results show that the proposed method can efficiently evaluate the stress distribution and stress extremum in structural steel members.